2023
DOI: 10.2196/42652
|View full text |Cite
|
Sign up to set email alerts
|

Robots in Assisted Living Facilities: Scoping Review

Abstract: Background Various technological interventions have been proposed and studied to address the growing demand for care of residents in assisted living facilities, in which a preexisting shortage of professional caregivers has been exacerbated by the COVID-19 pandemic. Care robots are one such intervention with the potential to improve both the care of older adults and the work life of their professional caregivers. However, concerns about efficacy, ethics, and best practices in the applications of ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…A dearth of research exists on how robots might change geriatric care and the work environment within assisted living facilities. Trainum et al reported that care robots constitute an intervention that has the potential to improve the care of older adults and the work life of their professional caregivers [29]. In our previous study, we developed a drug distribution support device for caregivers, which was subsequently installed in a group home, and a 3-month monitoring experiment was conducted.…”
Section: Data Link Of Pill Dispenser and Phrmentioning
confidence: 99%
“…A dearth of research exists on how robots might change geriatric care and the work environment within assisted living facilities. Trainum et al reported that care robots constitute an intervention that has the potential to improve the care of older adults and the work life of their professional caregivers [29]. In our previous study, we developed a drug distribution support device for caregivers, which was subsequently installed in a group home, and a 3-month monitoring experiment was conducted.…”
Section: Data Link Of Pill Dispenser and Phrmentioning
confidence: 99%
“…9,10 These studies focusing on older adults as main beneficiaries are essential; however, multifaceted challenges should be further addressed for implementing ATs in care settings. 6 Several studies addressing this issue show that in addition to financial (e.g. expensive) and technological (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the existing studies on robotic ATs in real life/work settings, many studies focus on the impact of social robots to older adults, 6 such as PARO, a therapeutic animal robot, 7 and NAO, a humanoid robot for communication 8 . Another popular AT in research is exoskeleton devices for rehabilitation and walking aids 9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rehabilitation robotics facilitates robot-assisted therapy and automated recovery training ( Xue et al, 2021 ). Assistive robots aid individuals with physical limitations, either enhancing or compensating for functions, promoting independence, and lessening the burden on caregivers ( Trainum et al, 2023 ). Additionally, robotic systems can automate hospital operations, spanning service robots aiding clinicians to robots in labs for high-throughput testing ( Kwon et al, 2022 ).…”
mentioning
confidence: 99%